(untitled) (مجلة علوم الرياضة الدولية, 2025)
Coenzyme Q10, a naturally occurring antioxidant, is believed to play a significant role in cellular energy production and protection against oxidative stress. This study aimed to investigate the efficacy of Coenzyme Q10 supplementation on various functional and biochemical variables, as well as aerobic capacity in basketball players. An experimental design was employed, and the sample consisted of basketball players from the University of Mustansiriya team, who were divided into a control and an experimental group. The control group received a placebo in the form of capsules, while the experimental group was given Coenzyme Q10 supplementation for 10 weeks. The main results indicate that Coenzyme Q10 supplementation had a positive effect on the variables studied. The researcher recommended that coaches pay attention to providing players with essential supplements, including Coenzyme Q10.